Final answer:
To factor completely the expression 64y^6-48y^3+9, we can use the formula for factoring a difference of cubes: a^3 - b^3 = (a - b)(a^2 + ab + b^2).
Step-by-step explanation:
To factor completely the expression 64y^6-48y^3+9, we can use the formula for factoring a difference of cubes: a^3 - b^3 = (a - b)(a^2 + ab + b^2). In this case, a = 4y^2 and b = 3. So we have:
64y^6 - 48y^3 + 9 = (4y^2 - 3)((4y^2)^2 + (4y^2)(3) + (3)^2) = (4y^2 - 3)(16y^4 + 12y^2 + 9).
This expression is now completely factored.